Development of the Italian Version of the Near-Death Experience Scale - Pistoia, Francesca; Mattiacci, Giulia; Sarà, Marco; Padua, Luca; Macchi, Claudio; Sacco, Simona (Frontiers in Human Neuroscience, 2018)
Near-Death Experiences (NDEs) have been defined as any conscious perceptual experience occurring in individuals pronounced clinically dead or who came very close to physical death. They are frequently reported by patients surviving a critical injury and, intriguingly, they show common features across different populations. The tool traditionally used to assess NDEs is the NDE Scale, which is available in the original English version. The aim of this study was to develop the Italian version of the NDE Scale and to assess its reliability in a specific clinical setting. A process of translation of the original scale was performed in different stages in order to obtain a fully comprehensible and accurate Italian translation. Later, the scale was administered to a convenience sample of patients who had experienced a condition of coma and were, at the time of assessment, fully conscious and able to provide information as requested by the scale. Interrater and test-retest reliability, assessed by the weighted Cohen’s kappa (Kw), were estimated. A convenience sample of 20 subjects (mean age±SD 51.6±17.1, mean time from injury 8.4±10.8SD months) was included in the study. Interrater [Kw 0.77 (95% CI 0.67-0.87)] and test-retest reliability [Kw 0.96 (95% CI 0.91-1.00)] showed good to excellent values for the total scores of the Italian NDE scale and for subanalyses of each single cluster of the scale. An Italian Version of the NDE Scale is now available to investigate the frequency of NDE, the causes for NDE heterogeneity across different life-threatening conditions and the possible neural mechanisms underlying NDE phenomenology.